PENGARUH PEMBERIAN BOKASHI PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus Vulgaris L) - Putri, Nurlaili Seprina; Afrida; Dewirman Prima Putra (Jurnal Research Ilmu Pertanian, 2021)
Research on the effect of giving bokashi cow manure on the growth and yield of green beans (Phaseolus vulgaris L.) was conducted in Korong Gadang Village, Kuranji District, Padang City, West Sumatra Province. This trial starts from January to April 2020. The research objective was to obtain the best dose of bokashi cow manure on the growth and yield of green beans. This experiment used a randomized block design with 5 treatments and 5 groups totaling 25 experimental units. The experimental unit was a plot measuring 1.0 m x 1.5 m, each experimental unit consisted of 10 plants, with a spacing of 50 x 30 cm. Then a total of 125 plants, 5 plants per plot are used as sample plants for observation. The treatments given were several doses of bokashi cow manure, namely: A = 0 t.ha -1 (0 g.plot-1); B = 3 t.ha -1 (562.plot-1); C = 6 t.ha -1 (1125 g.plot-1); D = 9 t.ha -1 (1688 g.plot-1); E = 12 t.ha -1 (2250 g.plot-1). The data from the observations were statistically analyzed with variance (F test). If Fhit. > Ftab, then continued with the Duncan´s New Multiple Range Test (DNMRT) further test at a significant level of 5%. The results of the experiment showed that giving bokashi cow manure showed a very significant effect on all the observed parameters. Bokashi cow manure 12 t.ha-1 showed the best effect on the growth and yield of green beans (Phaseolus vulgaris L).